Simplified Computer Program for Ocean Wave Simulation - Idris, Ahmad; Sati Hamonangan Harahap, Indra; Osman Ahmed Ali, Montasir (International Journal of Engineering and Technology, 2018)
Analysis and design of structures located offshore involves the simulation of the ocean wave process in order to select a design load. This is a rigorous process that involves the solution of difficult mathematical equations. This study presents an efficient computer program for the simulation of the wave. The program was designed in such a way that only the wave parameters for a given location are required as input. The program then simulate the wave using Karhunen-Loeve series representation in which the eigenfunctions of Prolate Spheroidal Wave Functions are developed and used. The use of the program was demonstrated by simulating an example wave.